Author’s reply to the comment titled “Eosinophilic gastroenteritis: The new imitator” - Regina Arruda Leal; Leonardo Fayad; Daniella Serafin Couto Vieira; Teresa Maria Silva Figueiredo; Aldemar Lopes; Roberta de Oliveira Magalhães Carvalho; Esther Buzaglo Dantas-Corrêa; Leonardo de Lucca Schiavon; Janaína Luz Narciso-Schiavon (Turkish Journal of Gastroenterology, 2019)
-